Representasi Rumah Gadang Pada Karya Lukis Hamzah - Mukhtia Resfa; Suryanti Suryanti; Rica Rian (V-art: Journal of Fine Art, 2021)
This study discusses the representation of the rumah gadang presented by Hamzah in his paintings, viewed from an aesthetic point of view. This research will explain how the form of representation presented by Hamzah. In this study, qualitative methods used include observation, interviews, and literature study. In this study, we will review Hamzah's paintings based on the period from 2010-2020, so eight Hamzah paintings will be studied. Hamzah's paintings illustrate how the social life of the Minangkabau community has changed due to the changing times. Physical changes from the results of Minangkabau culture are changes that occur in the form of the rumah gadang. The visual of the rumah gadang is expressed in the forms of the rumah gadang that has been damaged, weathered, and even collapsed. Hamzah does not emphasize the forms of rumah gadang in one type only but symbolizes the symbolic rumah gadang. The representation of rumah gadang in Hamzah's painting can be analyzed that there are 3 visual types of rumah gadang in this study, namely the type of rumah gadang Gajah Maharam, Lipek Pandan and Balah Bubuang.